2015
DOI: 10.5665/sleep.4816
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sleep by Insulin-like Peptide System inDrosophila melanogaster

Abstract: Taken together, the results indicate that the Drosophila insulin-like peptide system is a crucial regulator of sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 43 publications
3
54
3
Order By: Relevance
“…In bumble bees and other insects, expression of insulin signalling pathway genes is an important regulator of diapause, and can be influenced by the cold temperatures experienced during queen overwintering (Amsalem, Galbraith, Cnaani, Teal, & Grozinger, ). However, insulin signalling is involved in other processes such as the sleep cycle, longevity, and sexual maturation, any of which may respond to aspects of seasonality that correlate with Isothermality (Cong et al, ; Post et al, ) . Although limited in number, other studies of montane adaptation in bees have suggested that the strongest signatures of selection may be in genes associated with olfaction, foraging, and reproduction (Montero‐Mendieta et al, ; Wallberg et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In bumble bees and other insects, expression of insulin signalling pathway genes is an important regulator of diapause, and can be influenced by the cold temperatures experienced during queen overwintering (Amsalem, Galbraith, Cnaani, Teal, & Grozinger, ). However, insulin signalling is involved in other processes such as the sleep cycle, longevity, and sexual maturation, any of which may respond to aspects of seasonality that correlate with Isothermality (Cong et al, ; Post et al, ) . Although limited in number, other studies of montane adaptation in bees have suggested that the strongest signatures of selection may be in genes associated with olfaction, foraging, and reproduction (Montero‐Mendieta et al, ; Wallberg et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The PDF + ventral lateral circadian neurons (LN v s) comprise a wake-promoting network that may potentially include NPF release from or feedback control via NPFR + to these cells (Parisky et al, 2008, Chung et al, 2009, Hermann et al, 2012, Kim et al, 2013)). The NPF + LN d circadian neurons, which may receive wake-promoting signals from the PDF + LN v s, have been previously implicated in the control of both starvation-induced sleep suppression and night time sleep regulation (Keene et al, 2010, Cong et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The IPCs have not been implicated in the direct control of circadian rest:activity rhythms, although insulin appears to act during development to modulate rest:activity rhythms in a Drosophila disease model (Cong et al 2015;Monyak et al 2016). In mammals, on the other hand, pancreatic β cells contain molecular clocks, and rhythmic secretion of insulin appears to be important for metabolic homeostasis (Van Cauter et al 1991;Boden et al 1996;Peschke and Peschke 1998).…”
mentioning
confidence: 99%